The Optimization of Spheroidizing Heat Treatment Parameters on SCM440 Alloy Steel Wires Using Taguchi Robust Design - Yang, Chih-Cheng; Lu, Yu-Ning; Sung, Chen-Lun (European Journal of Applied Sciences, 2022)
In the fastener industry, SCM440 alloy steel wire is widely used in the production of cold forging parts, such as high-strength steel fasteners, auto parts, hardware supplies, etc. The wire manufacturers use an intercritical process for spheroidized annealing the alloy steel wires. The quality of a spheroidized annealed wire affects the cold forging quality of fasteners. A series of experimental tests on SCM440 alloy steel wires is carried out in a commercial hydrogen furnace. Various parameters such as spheroidized annealing temperature (A), prolonged heating time (E), holding temperature and time (B, C), cooling rate and temperature (D, F) affect the quality characteristics of wires, such as tensile strength, hardness and ductility. The effects of intercritical spheroidized annealing treatment on mechanical properties are investigated using Taguchi robust design to obtain optimal spheroidized annealing conditions to improve the mechanical properties of alloy steel wires for cold forming. It is experimentally revealed that the spheroidized annealing temperature (A), cooling rate and temperature (D, F) significantly affect the quality of spheroidizing annealed SCM440 alloy steel wires. The optimal spheroidized annealing conditions for SCM440 alloy steel wire are spheroidized annealing temperature of 771°C and prolonged heating for 5.0 h, then holding the temperature of 725°C for 1.0 h, and slowly cooling to the temperature of 713°C at the rate of -9°C /h. Therefore, the optimal mean tensile strength of 520.0 MPa, optimal mean hardness of 80.8 HRB, and optimal mean ductility of 0.488 are obtained. The variations of the properties are significantly reduced to achieve a much even quality for annealed wires. The optimal spheroidizing heat treatment parameter settings evidently improve the performance measures and the cold formability of SCM440 alloy steel wires is effectively improved.